2003
DOI: 10.1023/a:1023954526639
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This preliminary study explored relationships between women's empowerment and HIV prevention on the national and individual level with a focus on Botswana. Among sub-Saharan Africa countries, HIV prevalence was positively correlated with indirect indicators of women's empowerment relating to their education (female enrollment in secondary education and ratio of female to male secondary school enrollment), but not to their economic status (female share of paid employment in industry and services) or political s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(31 citation statements)
references
References 23 publications
0
30
1
Order By: Relevance
“…Our finding of an association between serious poverty (insufficient food in the last week) and HIV infection is in line with the finding in a cross-sectional study in Botswana and Swaziland that women who reported insufficient food were also more likely to report risky sexual behaviours such as inconsistent condom use, transactional sex, and intergenerational sex [56], but at first glance contrasts with the finding from DHS surveys in sub-Saharan Africa that HIV prevalence was higher in wealthier households [57]. A small study in Botswana found economic independence to be strongly associated with negotiating power and condom use, whereas education was not a crucial factor [58]. Among those who had remunerated employment in our study, people with higher earning employment were at higher risk; this factor dropped out of the multivariate model including extreme poverty.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of an association between serious poverty (insufficient food in the last week) and HIV infection is in line with the finding in a cross-sectional study in Botswana and Swaziland that women who reported insufficient food were also more likely to report risky sexual behaviours such as inconsistent condom use, transactional sex, and intergenerational sex [56], but at first glance contrasts with the finding from DHS surveys in sub-Saharan Africa that HIV prevalence was higher in wealthier households [57]. A small study in Botswana found economic independence to be strongly associated with negotiating power and condom use, whereas education was not a crucial factor [58]. Among those who had remunerated employment in our study, people with higher earning employment were at higher risk; this factor dropped out of the multivariate model including extreme poverty.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Research now also shows that economic independence for women is a factor that is strongly related to negotiating safer sex. 37 Thus, the combination of HIV/AIDS prevention and economic initiates could produce important synergies that extend beyond the economic realm to “empower women” and provide more enduring protection from HIV/AIDS risks than HIV/AIDS prevention can do alone.…”
Section: Economic Empowermentmentioning
confidence: 99%
“…A number of reports from sub-Saharan Africa have revealed an association between violence, sexually transmitted infections (STIs) 6 and, more specifically, HIV infection in women. 7-13 A range of associations between domestic violence and HIV has also been documented. Acts of domestic violence, which include sexual assault, are frequently associated with STI infections such as bacterial vaginosis.…”
Section: Introductionmentioning
confidence: 99%